DAMPAK PANDEMI COVID-19 TERHADAP UMKM ( STUDI KASUS TERHADAP PENJUAL SEAFOOD DI KOTA MUARO SIJUNJUNG) - Arwin, Arwin (Program Studi Manajemen Bisnis Syariah STAIN Mandailing Natal, 2021)
This paper focuses on the impact of Covid-19 on Micro Enterprises and the strategies used by Seafood business actors to increase sales turnover during the Covid-19 pandemic. The research method used in this study is a qualitative research method, with data collection techniques in the form of direct interviews with Seafood business owners and from several other journal sources. The results of this study indicate that the impact of the Covid-19 pandemic on Micro Seafood Enterprises is quite high, namely an increase in sales turnover of 60 percent during the Covid-19 pandemic. This is because Seafood sellers use digital marketing to promote their product sales through social media and direct promotions to buyers directly at their Seafood tent. There are several ways that Seafood-selling Micro Businesses can do to survive and increase sales turnover during the pandemic, including e-commerce, digital marketing, improving product quality and service to consumers.